Pengaruh Kualitas Pelayanan Petugas Check-in Counter Terhadap Kepuasan Penumpang Super Air Jet di Bandar Udara Internasional Sultan Aji Muhammad Sulaiman (SAMS) Sepinggan Balikpapan - I Dewa Ayu Thiasita Pitaloka; Yunus Purnama (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The aviation industry in Indonesia has experienced rapid growth in line with the increasing demand for air transportation. One of the key aspects of airline service is the check-in process, which serves as the first interaction between passengers and the airline and plays a role in shaping the customer experience. This study aims to analyze the impact of check-in counter service quality on passenger satisfaction with Super Air Jet at Sultan Aji Muhammad Sulaiman (SAMS) Sepinggan International Airport, Balikpapan. This research employs a quantitative approach using a survey method, involving 100 passenger respondents who have used Super Air Jet at least once and are aged between 17 and 40 years. The survey was conducted at Sultan Aji Muhammad Sulaiman (SAMS) Sepinggan International Airport, Balikpapan. Data analysis was performed using validity tests, reliability tests, classical assumption tests, simple linear regression, T-tests, and the coefficient of determination (R²). The results of the study indicate that the quality of check-in counter service has a positive and significant impact on passenger satisfaction. The simple linear regression test shows a regression coefficient value of 0.351 with a correlation value of 0.942. Additionally, the T-test results show a calculated t-value of 20.931, which is greater than the critical t-value of 1.660, with a significance level of 0.000 < 0.05, thereby supporting the research hypothesis. Based on these findings, it can be concluded that improving service quality at the check-in counter plays a crucial role in enhancing passenger satisfaction.